QOL-57. AT HOME NEUROCOGNITIVE TESTING IS POSSIBLE IN PEDIATRIC BRAIN TUMOR PATIENTS. Issue 2 (22nd June 2018) - Rosenfeld, Amy; Etzl, Michael; Gieseking, Annie; Goodman, Amanda; Peterson, Dianne; Daniels, Thomas; Schmebri, Adrian; Harel, Brian
Abstract: BACKGROUND: Neurocognitive decline is a major cause of morbidity in pediatric brain tumor patients. Traditionally, testing to monitor this decline has been completed in a clinic setting. It is often difficult to obtain neurocognitive evaluations in clinic, and testing only in clinics limits the frequency of assessments. Cogstate is a brief computerized neurocognitive battery capable of being administered in unsupervised settings. We administered the Cogstate battery to off therapy brain tumor patients at home and in the clinic to evaluate its utility in monitoring cognition at home. MATERIALS/METHODS: Demographic data and QOL questionnaires were collected during the in clinic baseline visit, and the Cogstate battery was also completed. A week later, patients completed testing at home. DATA: Twenty-five patients enrolled on study and 19 completed both in clinic and at home assessments. Mean age at diagnosis was 9.8 years, and at study enrollment was 13.0 years. Diagnoses included High Risk Medulloblastoma (n=7), Standard Risk Medulloblastoma (n=1), Ependymoma (n=4), Choroid Plexus Carcinoma (n=1), Ganglioglioma (n=3), Germinoma (n= 1), Nongerminomatous Germ Cell Tumor (n=2), Anaplastic Astrocytoma (n=1), Juvenile Pilocyctic Astrocytoma (n=3), Dysembroplastic Neuroepithelial Tumor (n=1), and Protoplasmic Astrocytoma (n=1). Thirteen patients received chemotherapy and 17 received radiation. All patients successfully completed testing and appeared able to understand the task requirements. No differences were observed between testing done in the clinic and at home. CONCLUSION: It appears possible to monitor cognition over time on a frequent basis in pediatric brain tumor patients. This has significant implications for clinical trials and clinical medicine.